Structure Characteristics of Light Cluster Nuclei with Extra Nucleons - Grinyuk, B.E.; Simenog, I.V. (Ukrainian Journal of Physics, 2022)
The cluster nuclei 6Li, 6He, 10Be, and 10C are studied as systems consisting of α-particles and two extra nucleons. The structure functions of these nuclei are found within the variational approach. The charge density distributions, form factors, and pair correlation functions are presented and explained.